AN EVALUATION OF ROCK SLOPE STABILITY USING LIMIT EQUILIBRIUM ANALYSES - Faridha Aprilia; I Gde Budi Indrawan (Geological Engineering Department Universitas Gadjah Mada, 2015)
The stability of rock slopes is controlled by several factors, such as the intact rock strength, discontinuity characteristics, groundwater condition, and slope geometry. Limit equilibrium (LE) analyses have been commonly used in geotechnical practice to evaluate the stability of rock slopes. A number of methods of LE analyses, ranging from simple to sophisticated methods, have been developed. This paper presents stability analyses of rock slopes at the Batu Hijau open mine in Sumbawa Barat using various methods of LE analyses. The LE analyses were conducted at three cross sections of the northern wall of the open mine using the Bishop Simplified, Janbu Simplified, Janbu Generalised, and General Limit Equilibrium (GLE) methods in Slide slope stability package. In addition, a Plane Failure (PF) analysis was performed manually. Shear strength data of the discontinuity planes used in the LE analyses were obtained from back analyses of previous rock slope failures. The LE analysis results showed that the rock slopes were likely to have shallow non-circular critical failure surfaces. The factor of safety (Fs) values obtained from the Bishop Simplified, Janbu Simplified, Janbu Generalised, and GLE methods were found to be similar, while the Fs values obtained from the PF method were higher than those obtained from the more rigorous methods. Keywords: Batu Hijau mine, Bishop Simplified, Janbu Simplified, Janbu Generalised, limit equilibrium analyses, general limit equilibrium, rock slope stability, plane failure.